The Use of Rice Husk Silica in Modified Zinc Oxide Photocatalysts to Reduce Chromium Concentration - Diana Rakhmawaty Eddy; L Ahmad Na’ani; Rustaman Rustaman; Solihudin Solihudin (Syarif Hidayatullah State Islamic University, 2020)
Rice husk ash contains approximately 90-98% dry weight of silica and they have been reported to have several advantages compared to mineral silica. One of these is its application as a filler in ZnO photocatalysts using the sol-gel method. This study was, therefore, conducted to determine the effect of adding rice husk silica to increase the ability of ZnO/SiO2 photocatalyst to reduce chromium concentration. Meanwhile, a previous effort has been made to degrade methylene blue dyes by 89%. This current research involved preparing rice husk charcoal using pyrolysis tubes after which they were extracted to produce silica while ZnO/SiO2 composites were made at a 95/5, 90/10, and 85/15 (w/w) ratio and composite activity test was conducted to determine its ability to reduce chromium concentration from practicum discharge. The SEM-EDS results showed the formation of SiO2 composites in ZnO while 82.6% decrease in total chromium concentration from waste was obtained after 2 hours irradiation with 95/5 composites using ultraviolet radiation.